Sodium capture mechanism by simulated silica/aluminosilicate slag at high temperatures. (15th November 2022) - Hu, Xinglei; Zhang, Zhongxiao; Wu, Xiaojiang; Fan, Haojie; Li, Zixiang; Kong, Chengdong; Jiang, Yanchi; Guo, Xinwei
Highlights: Transition of Al-VI to Al-IV/Al-V in aluminosilicate is a prerequisite for Na capture. The SCE of pure SiO2 and Al2 O3 is lower than aluminosilicate at high temperatures. There exist optimal ratios of CaO and MgO in aluminosilicates for Na capture. The addition of Fe2 O3 in aluminosilicates inhibits sodium capture. Abstract: This paper aims to clarify the sodium capture mechanism by silica/aluminosilicate slag under conditions of cyclone combustion process of high-alkali coal. A series of simulated silica and aluminosilicate slag containing various proportions of SiO2, Al2 O3, CaO, MgO, Fe2 O3 and NaCl were prepared and exposed in a tube furnace at 1300–1500 °C to simulate a cyclone combustion environment. Results show that the transition from six-coordinated Al (Al-VI) to four- and five-coordinated Al (Al-IV and Al-V) is an essential step for the sodium capture process by molten aluminosilicates. The aluminosilicate with a molar ratio of SiO2 to Al2 O3 (Si/Al) between 3:1 and 10:1 shows the best Na capture performance due to the complete transition of Al in it. Beyond this range, excess Al-VI or SiO2 will be produced and reduce the sodium capture ability of aluminosilicate. A small amount of CaO or MgO in the aluminosilicates can promote sodium capture efficiency (SCE) due to their fluxing effects. Whereas high content of CaO or MgO will inhibit the Na capture owing to the competing reactions with aluminosilicate between Ca/Mg and Na. The existence of Fe2 O3 can strongly inhibit the Na capture, which is probably caused by the fact that the structures of Na-[Fe-O-Si] and Na-[Fe-O-Al] pair are less stable than that of Na-[Si-O-Si] and Na-[Al-O-Si].